2021
DOI: 10.3390/antiox10040538
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Hazelnut Peels on the Contents of Fatty Acids, Cholesterol, Tocopherols, and on the Shelf-Life of Ripened Ewe Cheese

Abstract: Hazelnut peel (HNP), a by-product from the chocolate industry, is considered to be a suitable ingredient to be included in the diet of ruminants. This study aimed to evaluate the effect of feeding dairy ewes with a diet containing HNP on ripened cheese quality, including fatty acid (FA) profile, cholesterol, and tocopherol content, as well as stability during storage under commercial conditions. In total, 10 experimental cheeses were produced with bulk milk obtained from ewes fed a commercial concentrate (C gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…The intake of oils resulting in a variety of metabolic disorders in the body. The onset of problems in metbolism in the body will have implications for the emergence of various diseases (Kimura et al .,2020;Marino et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The intake of oils resulting in a variety of metabolic disorders in the body. The onset of problems in metbolism in the body will have implications for the emergence of various diseases (Kimura et al .,2020;Marino et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Hampir sebagian besar pengolahan makanan menggunakan minyak. Penggunaan minyak yang terus menerus dan pada suhu tinggi dapat menyebabkan kerusakan pada minyak (Bouaid et al, 2016;Liu et al, 2019;Marino et al, 2021). Minyak goreng yang terpapar suhu tinggi dalam waktu lama akan berubah menjadi asam lemak dan radikal bebas yang dapat menyebabkan beragam penyakit pada tubuh (Bhatnagar et al, 2009;Surtini & Badriyah, 2021).…”
unclassified
“…This is a by-product from the chocolate industry and is rich in phenolic compounds. The data showed that cheese from hazelnut peel supplemented ewes has a healthier lipid profile and higher tocopherol content [ 18 ].…”
mentioning
confidence: 99%